(untitled) (REMUNOM, 2024)
This article discusses teleharassment, which is very relevant nowadays, especially considering the increased use of communication technologies. Teleharassment has a significant impact on people’s lives, and has psychological and social consequences, and in addition to the emotional and psychological impact, teleharassment can lead to mental health problems, such as stress, anxiety and depression. Constantly receiving offensive, threatening or humiliating messages can significantly affect a worker’s well-being and productivity, creating a toxic and harmful work environment. These consequences can affect not only the worker’s personal life, damaging their quality of life and their relationships with others. Another point is the opportunity to analyze the dynamics of virtual harassment, how it is established within the virtual work sphere, and its legal consequences.